2006
DOI: 10.1186/1471-2458-6-92
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of metabolic syndrome-related disorders in a large adult population in Turkey

Abstract: Background: There are few existing large population studies on the epidemiology of metabolic syndrome-related disorders of Turkey. The purpose of this study was to assess the prevalence of metabolic syndrome-related disorders in the Turkish adult population, to address sex, age, educational and geographical differences, and to examine blood pressure, body mass index, fasting blood glucose and serum lipids in Turkey.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
54
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(70 citation statements)
references
References 33 publications
12
54
4
Order By: Relevance
“…Among the subjects with MS, the prevalence of high blood pressure and hyperglycemia were higher in Turkey than in the USA. In contrast, the prevalence of abdominal obesity, low HDL and hypertriglyceridemia were lower in our population compared with population of the USA (Sanisoglu et al, 2006). Prevalence of other components of MS in Turkish population and US subjects was not much different.…”
Section: Components Of Mscontrasting
confidence: 72%
See 1 more Smart Citation
“…Among the subjects with MS, the prevalence of high blood pressure and hyperglycemia were higher in Turkey than in the USA. In contrast, the prevalence of abdominal obesity, low HDL and hypertriglyceridemia were lower in our population compared with population of the USA (Sanisoglu et al, 2006). Prevalence of other components of MS in Turkish population and US subjects was not much different.…”
Section: Components Of Mscontrasting
confidence: 72%
“…Similar to our results, they reported the prevalence of the MS was 33.4% and was more common in women than in men (39.1 vs 23.7). Sanisoglu et al (2006) recently reported a prevalence of 27.38% for MS that is apparently low for our country. However, their study was designed to investigate the nutrition status of the population, not the prevalence of MS.…”
Section: Discussionmentioning
confidence: 65%
“…Incidence of metabolic syndrome increases as age progresses. In a study in Turkey, the prevalence of the metabolic syndrome was 15.3%, 23.1%, 28.0%, 26.0%, and 20.5% among people aged from 30 to 39, 40 to 49, 50 to 59, 60 to 69, 70 to 79 and ≥ 80 years old, respectively [17]. Study in Norway showed that prevalence of the metabolic syndrome elevated with age into the ninth decade of life [18].…”
Section: Introductionmentioning
confidence: 98%
“…Its incidence and prevalence have risen dramatically, especially in the western countries, as a result of the increasing prevalence of obesity [5]. As in schizophrenia, there is great concern about the prevalence of metabolic syndrome in patients with bipolar disorder, although research in this area is scarce [6]. Study by Fagiolini et al [7] of 171 subjects revealed a prevalence of metabolic syndrome in bipolar disorders as high as 30% compared to the general population.…”
Section: Introductionmentioning
confidence: 99%
“…There is a statistically significant association between atypical antipsychotics and metabolic syndrome. However, there are no such association between mood stabilizers and metabolic syndrome [6]. This study evaluates the prevalence of metabolic syndrome in 32 patients with bipolar disorder that are either on Li or VPA monotherapy.…”
Section: Introductionmentioning
confidence: 99%